The Influence of Promotional Activities via Instagram Application Utilising Multiple Image & Video Post Features and Customer Testimonials on Consumer Purchase Decisions - Halawa, Kalvin Getianus (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the influence of promotions through the Instagram application with multiple image & video posts and customer testimonials on consumer purchasing decisions. The growth of internet and social media usage in Indonesia has changed marketing patterns and consumer behavior, with Instagram becoming the dominant platform in digital marketing strategies. The diverse visual content through the multiple image & video posts feature allows marketers to present product information more comprehensively, while customer testimonials serve as social proof that can build consumer trust. This study uses a quantitative methodology with a survey approach through questionnaires distributed to active Instagram users. Data analysis was conducted using multiple linear regression to test the simultaneous and partial effects of the two independent variables on purchase decisions. The results indicate that Instagram promotions with multiple image and video posts have a positive and significant impact on purchase decisions. Similarly, customer testimonials are proven to have a significant influence on consumer purchase decisions. Simultaneously, both variables contribute substantially to explaining variations in consumer purchasing decisions. These findings confirm the importance of integrating visually appealing content strategies with authentic customer testimonials in digital marketing to enhance promotional effectiveness and drive consumer purchasing decisions.